The relationship between onset of blood lactate accumulation, critical velocity, and maximal lactate steady state in soccer players - Denadai, B. S.; Gomide, E. B. G.; Greco, C. C. (The Journal of Strength and Conditioning Research, 2005)
The objective of this study was to analyze the validity of the velocity corresponding to the onset of blood lactate accumulation (OBLA) and critical velocity (CV) to determine the maximal lactate steady state (MLSS) in soccer players. Twelve male soccer players (21.5 ± 1.0 years) performed an incremental treadmill test for the determination of OBLA. The velocity corresponding to OBLA (3.5 mM of blood lactate) was determined through linear interpolation. The subjects returned to the laboratory on 7 occasions for the determination of MLSS and CV. The MLSS was determined from 5 treadmill runs of up to 30-minute duration and defined as the highest velocity at which blood lactate did not increase by more than 1 mM between minutes 10 and 30 of the constant velocity runs. The CV was determined by 2 maximal running efforts of 1,500 and 3,000 m performed on a 400-m running track. The CV was calculated as the slope of the linear regression of distance run versus time. Analysis of variance revealed no significant differences between OBLA (13.6 ± 1.4 km/h) and MLSS (13.1 ± 1.2 km/h) and between OBLA and CV (14.4 ± 1.1 km/h). The CV was significantly higher than the MLSS. There was a significant correlation between MLSS and OBLA (r = 0.80), MLSS and CV (r = 0.90), and OBLA and CV (r = 0.80). We can conclude that the OBLA can be utilized in soccer players to estimate the MLSS. In this group of athletes, however, CV does not represent a sustainable steady-state exercise intensity.